2008
DOI: 10.1128/aem.02689-07
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification and Typing of Listeria Species by Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry

Abstract: Listeria monocytogenes is a food-borne pathogen that is the causative agent of human listeriosis, an opportunistic infection that primarily infects pregnant women and immunologically compromised individuals. Rapid, accurate discrimination between Listeria strains is essential for appropriate therapeutic management and timely intervention for infection control. A rapid method involving matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) that shows promise for identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
168
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(181 citation statements)
references
References 44 publications
6
168
0
7
Order By: Relevance
“…Whole-cell matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) (31) is an emerging technology for identification of bacteria (26,46), fungi (17,33), viruses (29,51), insects (41), and helminths (42). MALDI-TOF MS-based identification can accurately resolve bacterial identity at the genus, species, and in some taxa subspecies levels (e.g., Salmonella enterica serovars, Listeria genotypes) (1,18). Identity is based on unique mass/charge ratio (m/z) fingerprints of proteins, which are ionized using short laser pulses directed to bacterial cells obtained from a single colony embedded in a matrix.…”
Section: P Agglomerans Is a Composite Taxon Conglomerating Formermentioning
confidence: 99%
“…Whole-cell matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) (31) is an emerging technology for identification of bacteria (26,46), fungi (17,33), viruses (29,51), insects (41), and helminths (42). MALDI-TOF MS-based identification can accurately resolve bacterial identity at the genus, species, and in some taxa subspecies levels (e.g., Salmonella enterica serovars, Listeria genotypes) (1,18). Identity is based on unique mass/charge ratio (m/z) fingerprints of proteins, which are ionized using short laser pulses directed to bacterial cells obtained from a single colony embedded in a matrix.…”
Section: P Agglomerans Is a Composite Taxon Conglomerating Formermentioning
confidence: 99%
“…Durch entsprechende Erg ä nzungen der Referenz-Spektren der Datenbanken konnte eine nahezu 100 % Identifi zierungsrate von Neisserien [11] , Clostridien [12] , Mycobakterien [13] , Salmonellen [14] , vergr ü nenden Streptokokken [15] und Helicobacter pylori [16] erreicht werden. W ä hrend das MALDI-TOF MS-System im Vergleich zu biochemischen Testsystemen im Bereich der Differenzierung von Enterobakterien, Staphylokokken und Streptokokken vergleichbar gute Ergebnisse liefert, zeigt es deutliche Vorteile bei der Differenzierung von Gram-positiven St ä bchen [17] , Anaerobiern und einigen Nonfermentern [18,19] . Insbesondere bei solchen Erregern, die sich durch lange Kultivierungszeiten auszeichnen, hat die MALDI-TOFbasierende Diagnostik eindeutige Zeitvorteile gebracht, die die Zeit bis zum Differenzierungsergebnis im Laboralltag drastisch reduziert haben.…”
Section: Einsatz Der Maldi-tof Massenspektrometrie In Der Mikrobiologunclassified
“…These works (Bernardo et al, 2002;Bright et al, 2002;Keys et al, 2004;Mandrell et al, 2005;Donohue et al, 2006;Carbonnelle et al, 2007;Barbuddhe et al, 2008;Grosse-Herrenthey et al, 2008;Hazen et al, 2009;Alispahic et al, 2010;Ayyadurai et al, 2010;Dubois et al, 2010;Stephan et al, 2010;Stephan et al, 2011). Furthermore, some studies were aimed at the detection of foodborne pathogens and food spoilage bacteria, including genera such as Escherichia, Yersinia, Proteus, Morganella, Salmonella, Staphylococcus, Micrococcus, Lactococcus, Pseudomonas, Leuconostoc and Listeria (Mazzeo et al, 2006).…”
Section: Maldi-tof Ms Fingerprinting a Rapid And Reliable Methods Formentioning
confidence: 99%
“…It has been shown that, when applying the same culture conditions, sample preparation, matrix, organic solvents and MALDI-TOF MS analyzer, reproducible spectral profiles are obtained (Keys et al, 2004;Barbuddhe et al, 2008). Although, different protocols can lead to a high variability in the resulting spectral profiles, it has to be mentioned that some peaks were detected, even if different protocols were applied.…”
Section: Sample Preparation Protocolmentioning
confidence: 99%